Respostas
Resposta:
x + 2y = 8 (1)
2x - y = 6 (2)
Isolando x em (1) e substituindo em (2)
x = 8 - 2y
2x - y = 6
2(8 - 2y) - y = 6
16 - 4y - y = 6
16 - 5y = 6
-5y = 6 - 16
-5y = -10
y = -10/-5
y = 2
x = 8 -2y
x = 8 - 2*2
x = 8 - 4
x = 4
Resposta:
S = {(x, y)} = {(4, 2)}
Explicação passo-a-passo:
.
. x + 2y = 8......=> x = 8 - 2y (troca na outra)
. 2x - y = 6
.
. 2x - y = 6
. 2.(8 - 2y) - y = 6
. 16 - 4y - y = 6
. - 5y = 6 - 16
. - 5y = - 10............=> y = 2 x = 8 - 2y
. x = 8 - 2 . 2
. x = 8 - 4
. x = 4
.
(Espero ter colaborado)